Peran Usaha Mikro Kecil Menengah (UMKM) Tahu Dalam Meningkatkan Kesejahteraan Masyarakat (Studi UMKM TAHU Desa Mendis Kabupaten Musi Banyuasin) - Arsyi Anistia Safari; Efni Anita; Ahmad Syahrizal (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
The number of MSMEs in Musi Banyuasin Regency has reached hundreds, it is hoped that this will increase the economy through opening business fields for the local community. The purpose of this study 1) to determine the role of Mendis in improving the community's economy. 2) to find out the supporting and inhibiting factors of Mendis in an effort to improve the community's economy. This study uses a qualitative method. The results of this study indicate 1) Mendis in Mendis Village, Musi Banyuasin Regency have a positive impact on society, including opening up job opportunities and employment opportunities, increasing people's welfare. 2) The supporting factors for Mendis are government support and enthusiasts from the results of Mendis which are food (tofu) itself. 3) The inhibiting factors for Mendis are capital, limited raw materials, weather, number of employees and business networks. The government is expected to pay more serious attention in efforts to support the progress of Mendis, to provide guidance, assistance, and training for Mendis so that they can compete in market competition. It is hoped that Mendis actors will be more innovative and able to adapt to the use of more sophisticated technology in order to obtain more effective and efficient results.